2008
DOI: 10.1017/s1743921309030440
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic reconnection and energy release on the Sun and solar-like stars

Abstract: Abstract. Magnetic reconnection is thought to play an important role in liberating free energy stored in stressed magnetic fields. The consequences vary from undetectable nanoflares to huge flares, which have signatures over a wide wavelength range, depending on e.g. magnetic topology, free energy content, total flux, and magnetic flux density of the structures involved. Events of small energy release, which are thought to be the most numerous, are one of the key factors in the existence of a hot corona in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Ultimately, we are left with the question: what caused the coherent gyrophase bunching in these energetic electron distributions? Torbert et al (2018) and Egedal et al (2019) both determined that this reconnection event observed by MMS on July 11, 2017 was consistent with 2-dimensional, symmetric, antiparallel reconnection, which is important since it indicates that the fields around the EDR in question were coherently structured and not dominated by turbulent fluctuations (e.g., Figure 2o from Torbert et al [2018] and Figure 2 from Egedal et al [2019]). J.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Ultimately, we are left with the question: what caused the coherent gyrophase bunching in these energetic electron distributions? Torbert et al (2018) and Egedal et al (2019) both determined that this reconnection event observed by MMS on July 11, 2017 was consistent with 2-dimensional, symmetric, antiparallel reconnection, which is important since it indicates that the fields around the EDR in question were coherently structured and not dominated by turbulent fluctuations (e.g., Figure 2o from Torbert et al [2018] and Figure 2 from Egedal et al [2019]). J.…”
Section: Discussionmentioning
confidence: 66%
“…Only FEEPS data from MMS-1, -2, and -3 are shown and discussed here due to limitations from sunlight contamination in FEEPS on MMS-4. As reported by Torbert et al (2018), the X-line was oriented such that the L-, M-, and N-directions (Denton et al, 2018) were approximately parallel to X-, Y-, Z-GSE directions, and the reconnection involved a weak guide field (|B M |/|B L | ∼4%; note also that the guide field was estimated as even weaker, ∼0.6%, by Egedal et al [2019]). When observed by MMS, the X-line was receding tailward (i.e., in the negative X-GSE direction) at approximately 170 km/s.…”
Section: Data Observations and Analysismentioning
confidence: 60%
See 1 more Smart Citation
“…For the eruption to occur, the magnetic balance must be disrupted in favor of the upward-directed pressure force. Discussions of ideas for eruption onset mechanisms are presented in detail in several works and reviews, including van Driel-Gesztelyi et al (2002); Klimchuk (2001); Linker et al (2003); Forbes et al (2006); Moore & Sterling (2006); van Driel-Gesztelyi (2009). Recently the consensus is that a "storage and release of energy" process occurs, where possible methods to release the energy are numerous.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the large number of studies of these processes, carried out by both data analyses (van Driel-Gesztelyi 2002;Zuccarello et al 2009) and numerical simulations (Cheung et al 2008, and references therein), several aspects remain unclear. For instance, it remains unclear the role played by the so-called moving magnetic features (MMFs, hereafter), small magnetic-flux concentrations, which are usually observed streaming out from the sunspot penumbra, later interacting with the ambient magnetic field, and then disappearing (Sheeley 1969;Harvey & Harvey 1973).…”
Section: Introductionmentioning
confidence: 99%